2023
DOI: 10.21203/rs.3.rs-3148213/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Family Planning Integration in Ethiopia’s Primary Health Care System: A qualitative study on opportunities, challenges and best practices

Addisalem Titiyos,
Yohannes Mehretie,
Yibeltal Kiflie Alemayehu
et al.

Abstract: Background Family planning (FP) service integration into primary health care (PHC) is an effective approach to improve FP use, and maternal and child health outcomes. The Ethiopian government promotes integration of FP services into primary health care. However, there is paucity of evidence on the status of FP service integration. The aim of this study is to explore the state of FP integration into PHC services and identify facilitators and barriers to integration. Methods A qualitative study nested with a l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, progress toward fully integrating FP into RMNCAH-N services at various levels of Ethiopia's primary healthcare system, particularly in facility settings is still slowly (13). The health extension worker program and a few initiatives to integrate FP into HIV and AIDS care are the only exceptions to date (14). To worst case various studies indicated that the health care needs of mobile pastoralists have been less addressed compared to agrarian and settled communities in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…However, progress toward fully integrating FP into RMNCAH-N services at various levels of Ethiopia's primary healthcare system, particularly in facility settings is still slowly (13). The health extension worker program and a few initiatives to integrate FP into HIV and AIDS care are the only exceptions to date (14). To worst case various studies indicated that the health care needs of mobile pastoralists have been less addressed compared to agrarian and settled communities in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%